Nick and Tesla's solar-powered showdown : a mystery with sun-powered gadgets you can build yourself - Pflugfelder, Bob, 1967- (Quirk Books, 2016)
"Super-smart kid inventors Nick and Tesla Holt have outsmarted crooks, spies, and kidnappers, but now it's time to crack their biggest mystery yet: where the heck are their parents? With the help of their eccentric Uncle Newt, the twins trace the clues to their missing Mom and Dad, scientists working on solar-power research for a clandestine government project. They'll need all their wits, along with an assortment of homemade gadgets, to outsmart the criminal mastermind who's trying to turn solar power into a secret weapon. Featuring instructions for building and using five awesome solar-powered contraptions--a hot dog cooker, alarm bell, listening device, model car, and nighttime LED signal cannon--this sixth installment is sure to please budding scientists and sleuthers alike."--